1986
DOI: 10.1002/ajh.2830210212
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic malignancy in sickle cell disease: Report of four cases and review of the literature

Abstract: Hematologic malignancy has rarely been reported in adults with sickle cell disease. We describe four sickle cell patients (two with hemoglobin SC, two with hemoglobin SS) who developed hematologic malignancy (acute myeloblastic leukemia, multiple myeloma, malignant histiocytosis, and Hodgkin's disease). Three of the cases represent the first adult association between SC or SS hemoglobinopathy and the particular malignancy involved. Sickle hemoglobin does not appear to exert a protective effect against childhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 24 publications
1
42
1
Order By: Relevance
“…In 1986, Stricker et al [13] reported four adult cases of cancer in SCD and summarized 13 previously reported cases of leukemia and lymphoma. They concluded that SCD likely not only provided no increased risk of cancer developing but also conferred no protection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1986, Stricker et al [13] reported four adult cases of cancer in SCD and summarized 13 previously reported cases of leukemia and lymphoma. They concluded that SCD likely not only provided no increased risk of cancer developing but also conferred no protection.…”
Section: Discussionmentioning
confidence: 99%
“…The development of malignancy in persons with SCD has been documented by numerous individual cases [8][9][10][11][12][13][14][15] and several small series [13][14][15] over the past 50 years. These scattered reports document that malignancy occurs in both children and adults with SCD but do not provide complete data on the types of cancer or attempt to define the incidence of cancer in this patient population [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that HU is genotoxic (Flanagan et al, 2010;Juul et al, 2010;Santos et al, 2011) while other studies suggest that HU has low mutagenicity in vivo (Stricker et al, 1986;Dawkins et al, 1997;Montalembert et al, 1999;Hanft et al, 2000;Montalembert, Davies, 2001;Moschovi et al, 2001). In this study, patients with SCA treated with HU had significantly elevated DI values when compared with the patients with SCA who were not treated with HU.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Many of these malignancies may benefit from autologous hematopoietic stem cell transplantation. However, filgrastim administered to mobilize hematopoietic stem cells may precipitate severe and sometimes fatal sickle crisis in patients with sickle-cell anemia or complex sickle-cell hemoglobinopathies.…”
mentioning
confidence: 99%